2022
DOI: 10.1093/brain/awab318
|View full text |Cite
|
Sign up to set email alerts
|

Naming-related spectral responses predict neuropsychological outcome after epilepsy surgery

Abstract: This prospective study determined the use of intracranially recorded spectral responses during naming tasks in predicting neuropsychological performance following epilepsy surgery. We recruited 65 patients with drug-resistant focal epilepsy who underwent preoperative neuropsychological assessment and intracranial EEG recording. The Clinical Evaluation of Language Fundamentals evaluated the baseline and postoperative language function. During extra-operative intracranial EEG recording, we assigne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 89 publications
2
43
0
Order By: Relevance
“…This finding has the potential to drastically improve extra-operative mapping for pediatric focal epilepsy patients, since electrical stimulation mapping is not always efficacious in young children ( Haseeb et al, 2007 ) and was reported to localize language areas in less than 20% of those younger than ten years old ( Schevon et al, 2007 ). Measurement of event-related high-gamma modulations is widely practiced in tertiary epilepsy surgery centers but previously reported tasks may not have been entertaining for children ( Crone et al, 2011 ; Lachaux et al, 2012 ; Arya et al, 2018 ; Mooij et al, 2016 ; Sonoda et al, 2022 ). In our current study, patients made an average of 221.4 responses during five-minute gameplay sessions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding has the potential to drastically improve extra-operative mapping for pediatric focal epilepsy patients, since electrical stimulation mapping is not always efficacious in young children ( Haseeb et al, 2007 ) and was reported to localize language areas in less than 20% of those younger than ten years old ( Schevon et al, 2007 ). Measurement of event-related high-gamma modulations is widely practiced in tertiary epilepsy surgery centers but previously reported tasks may not have been entertaining for children ( Crone et al, 2011 ; Lachaux et al, 2012 ; Arya et al, 2018 ; Mooij et al, 2016 ; Sonoda et al, 2022 ). In our current study, patients made an average of 221.4 responses during five-minute gameplay sessions.…”
Section: Discussionmentioning
confidence: 99%
“…We measured event-related high-gamma activity, as reported in our previous studies ( Mitsuhashi et al, 2021 ; Sonoda et al, 2022 ). Using the FieldTrip toolbox ( http://www.fieldtriptoolbox.org/ ), we performed the Morlet wavelet time-frequency analysis on iEEG signals referenced to a common average ( Crone et al, 2001 ; Mitsuhashi et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations